Implementasi Pembuatan Sistem Informasi Artha Puspa dengan Framework Agile (Scrum) - Candra Pamungkas; Diva Yuannisa Nur Berlian; Nabila Renaldy; Fawwaz Naufaldini; Muhammad Nur Yasin (Yayasan Literasi Sains Indonesia, 2023)
In the business world where companies use Information technology is important enough in the world of work to get work done easily to be more effective and efficient. An example of the development of information technology in the world of work and business is the data processing system. In the case study in Artha Puspa flower shop business using E-Commerce, on data processors. Our team designed a web-based Artha Puspa Flower buying and selling application which facilitates flower buying and selling transactions without being limited by location The method chosen here is the Agile method with continuous development in a process called Scrum which overcomes problems in the work more easily understood and transparently, allowing the team to check and adapt depending on current conditions. The implementation of the scrum method is built using the MySQL framework and database. The results of the research on the sales and purchase system at the web-based Artha Puspa Flower Shop facilitate transactions, so that customers can make buying and selling transactions through the website without time and place limits. Customers can make buying and selling transactions and make it easier for admins to make sales, with this Flower buying and selling system to support a wider market reach without location restrictions